DIGITAL TWIN OF FOLK ART MUSEUMS FOR EDUCATION - Ranjan, Nidhi; Singh, Ashishika; Singh, Namrata; Todkari, Vinod Chandrakant; Das, Debasish; Brar, Manvinder (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Embient digital twin technology in the cultural heritage preservation system has become a transformative method of learning and interaction in a folk museum of art. This paper suggests the development and execution of a Digital Twin Framework of Folk Art Museums that would contribute to increasing the accessibility to education, understanding of culture, and experience. The digital twin is capable of reflecting the physical conditions of things like temperature, humidity, and light through 3D scanning, IoT-enabled sensors, and an AI-driven knowledge graph, and to preserve and maintain an authentic context. Also, machine learning algorithms learn user interactions to customize education, and the virtual reality (VR) and augmented reality (AR) interface enables a person to explore folk art traditions and methods immersively. Moreover, the interactive simulations can allow students to study artistic procedures and cultural stories in the form of an interactive process that links the classical craftsmanship to digital pedagogy. This is a democratizing practice of folk art education, where remote learners and researchers are able to interact with cultural heritage without being constrained by geographical borders. The suggested system, therefore, becomes a sustainable, intelligent, and educationally enriched digital ecosystem, promoting cultural sustainability and creativity in learning in museums. The paper is able to conclude that digital twins signify a paradigm shift in the way folk art may be perceived, preserved and taught during the digital age.